Analysis of the Effect of Price on Purchase Decision through Promotion as a Mediating Variable : A Study at PT Capella Dinamika Nusantara Pekanbaru - Sari, Maya Rizki; Liaochunliu; Muda, Iskandar (Neraca Keuangan : Jurnal Ilmiah Akuntansi dan Keuangan, 2025)
At PT Capella Dinamika Nusantara Pekanbaru, this research aims to explore how pricing affects buying choices, with promotions acting as a middle factor. Building on a previous model that only looked at the direct influence of price and advertising on what consumers do, this study introduces a new approach. Data was collected from 100 people who bought Honda Beat motorcycles, chosen using the Slovin formula, and applied a quantitative method. The responses were evaluated using a five-point Likert scale, and the data was examined through Structural Equation Modeling (SEM) using the Partial Least Squares (PLS) method. The study shows that price has a strong influence and positively affects both marketing strategies and purchase decisions. Additionally, promotions are crucial in shaping how price impacts buying choices and significantly affect those decisions. These results suggest that just having a good price won’t necessarily increase the chance of a sale without strong marketing strategies. Therefore, businesses should implement marketing tactics that emphasize the significance of competitive pricing to influence consumer purchasing behavior.